Exploring students' argumentation skills using Instagram-based learning - Zayyinul Mushthofa; Susilo Susilo; Ellianawati Ellianawati (Universitas Ahmad Dahlan, 2022)
Instagram is one of the most popular social media for teenagers to get information through pictures and short videos. Instagram users often provide comments in response to the information obtained. Instagram can be used in online-based learning during the Covid 19 pandemic. This study aims to explore students' argumentation skills using Instagram-based learning and measure student satisfaction responses in using Instagram as a learning medium. The type of research used is descriptive quantitative. Respondents used in this study were 25 students of SMA Multazam IBS Semarang. The results of the study that obtained argumentation skills after learning to use Instagram were 56.13 with the indicator giving support getting the largest value of 82.00 and refutation having the smallest value of 44.00. The percentage of students who argue is 76%. Student responses to learning using Instagram 53% strongly agree, 40% agree, 6% disagree, the remaining 1% disagree.